Provision and Perception of Physiotherapy in the Nonoperative Management of Degenerative Cervical Myelopathy (DCM): A Cross-Sectional Questionnaire of People Living With DCM. Issue 4 (May 2022) - Butler, Max B.; Mowforth, Oliver D.; Badran, Abdul; Starkey, Michelle; Boerger, Timothy; Sadler, Iwan; Tabrah, Julia; Treanor, Caroline; Phys, Lucy Cameron Grad Dip; Kalsi-Ryan, Sukhvinder; Laing, Rodney J.; Davies, Benjamin M.; et al.
Study Design: Cross-sectional survey. Objectives: Degenerative cervical myelopathy (DCM) is a common syndrome of acquired spinal cord impairment caused by canal stenosis secondary to arthritic changes of the spine. International guidelines consider physiotherapy an option for mild, stable DCM; however, few studies have been conducted on nonoperative management. The objective was to determine current usage and perceptions of nonoperative physiotherapy for DCM. Methods: Persons with DCM were recruited to a web-based survey. Participants with complete responses that had not received surgery were included (n = 167). Variables included symptom duration, treatment history, current disability, and demographic characteristics. Results: Disease and demographic characteristics were equivalent between those who did and did not receive physiotherapy. In all, 19.5% of physiotherapy recipients reported subjective benefit from physiotherapy. Those perceiving benefit had significantly higher mJOA (modified Japanese Orthopaedic Association) scores, lower neck pain scores, and shorter symptom duration. In multivariate logistic regression analysis, those with mild DCM were more likely to perceive benefit than those with severe DCM, as were those with moderate DCM (to a lesser extent). Individuals whose diagnosis was delayed 1 to 2 years were less likely to perceive benefit than those that waited 0 to 6 months. Conclusions: The provision of nonoperative physiotherapy in the management of DCM is inconsistent and appears to differ from international guidelines. Few patients perceived benefit from physiotherapy; however, this was more likely in those with mild DCM and in those with shorter symptom durations. Further work is needed to establish the appropriate role of physiotherapy for this population.